Privy Council or a Caribbean final Court of Appeal. - RAWLINS, Hugh A. (1996)
Presents a historical background of the Privy Council in order to put the considerations of the setting up of a Caribbean Court of Appeal into perspective. Identifies factors which appear to be in favour of the setting up of such a court, as well as those which do not.